Mediation Legal Protection in Handling Minor Crimes - Shelly Adisti Setiawati; Maria Adelweys Niken Aprilia Sinaga; Jessica Zelma Adriela; Reva Naira; Indy Kanaishia; Jeane Neltje Saly (CV. Rayyan Dwi Bharata, 2023)
The position of the judiciary as the last place to seek justice has a very important role in the way of solving a case or problem through mediation peace. The first appearance of a mediation process was in 1970 in California where another name is usually Alternative Dispute Resolution (ADR) which was only practiced thoroughly in 1979. The purpose of writing is so that readers will understand the existence of mediation law with protection by means of criminal acts light through mediation, research methods that use the, journal writing with normative legal research methods. Approach to normative juridical means an approach using literature, doctrine, and document studies that have been made by the opinion of experts. In handling criminal acts, mediation can be an effective and useful alternative in cases of minor crimes.